The effect of service quality and relationship quality in-home service car repair and maintenance on customer loyalty - Devita Sari; Tengku Ezni Balqiah (President University, 2022)
The rapid growth of the automotive industry in recent years, especially in the car industry, has emphasized the accompanying role of service quality (assurance, empathy, tangibles, responsiveness, and reliability) in-home service car repair and maintenance. With a paradigm shift to relationship marketing, how to build relationship quality between customers and firms has become a key for companies to achieve success. This study aims to determine whether service quality and customer satisfaction, trust, and commitment as relationship quality factors can be valuable to companies in generating customer loyalty. In turn, the influence of their attitudinal loyalty and their behavioral loyalty in the future. Data was collected from 413 respondents who used the home service car repair and maintenance during the last six months. The conceptual model was analyzed using partial least square structural equation modeling (PLS-SEM). Findings confirm that trust significantly and positively impacts commitment and satisfaction. Home service car repair and maintenance service quality dimensions also influence trust, commitment, and satisfaction. The findings revealed that service quality and relationship quality influenced customer loyalty. Finally, customer satisfaction has the highest overall effect on attitudinal loyalty and behavioral loyalty. The findings of the study add to developing empirical literature on service quality, relationship quality, and customer loyalty. The study indicates how relationship quality factors can influence customer loyalty and assist in building long-term relationships with customers where post-home service car repair and maintenance are concerned.